Encouraging Reductions in Nonpoint Source Pollution through Point‐nonpoint Trading: The Roles of Baseline Choice and Practice Subsidies. (2nd May 2014) - Ribaudo, Marc; Savage, Jeffrey; Talberth, John
Abstract: Water quality regulations in the United States apply almost exclusively to point sources. In impaired watersheds where both point and nonpoint sources contribute to pollution, the U.S. Environmental Protection Agency (EPA) is encouraging the use of point‐nonpoint trading to reduce the cost of point sources to meet their permit requirement, and to encourage nonpoint sources to voluntarily contribute more towards meeting overall water quality goals. The EPA guidance encourages trading programs to set a nonpoint source eligibility baseline that extracts some "extra" abatement from nonpoint sources. Research has shown that setting an eligibility baseline that is substantially more stringent than current management could discourage nonpoint source participation and significantly hinder trading. In this paper we examine how choosing the eligibility baseline for agricultural sources affects the efficiency goal of trading (reducing costs to point sources), as well as how it affects the EPA goal of encouraging nonpoint abatement. Using data from the Chesapeake Bay Watershed we find that eligibility baselines set to encourage additional nonpoint source abatement reduce the supply of credits in a market; the more stringent the baseline, the fewer the trades and the smaller the overall abatement from nonpoint sources. A subsidy to farmers for reducing the cost of meeting a baseline encourages greater nonpoint source abatement, but may not benefit the trading market.